2014
DOI: 10.1007/s11356-014-2602-8
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in sediments, blue spotted tilapia Oreochromis leucostictus (Trewavas, 1933) and its parasite Contracaecum multipapillatum from Lake Naivasha, Kenya, including a comprehensive health risk analysis

Abstract: This study presents the distribution of 15 major and trace elements in sediments and fish and their pericardial parasites from Lake Naivasha, Kenya. The lake is one of the few freshwater lakes in the Great Rift Valley and is under strong anthropogenic pressure mainly due to agricultural activities. Its fish provide a valuable protein source for approximately 100,000 people in the area. Fish and their parasites have been acknowledged as indicators of environmental quality due to their accumulation potential for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
32
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 36 publications
11
32
3
Order By: Relevance
“…Otachi et al (2014) reported Li concentrations from freshwater fish for the first time, giving mean values of 299 mg/kg dw in the muscle of Oreochromis leuctostictus from Lake Naivasha, Kenya, a concentration higher but at least in the same order of magnitude as we found in H. forskahlii. The possible sequentially of Lithium has been under discussion in the recent past, but the evidence appears to be sufficient to accept lithium as essential at least for humans (Schrauzer 2002) and most probably other mammals (Anke et al 2005).…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…Otachi et al (2014) reported Li concentrations from freshwater fish for the first time, giving mean values of 299 mg/kg dw in the muscle of Oreochromis leuctostictus from Lake Naivasha, Kenya, a concentration higher but at least in the same order of magnitude as we found in H. forskahlii. The possible sequentially of Lithium has been under discussion in the recent past, but the evidence appears to be sufficient to accept lithium as essential at least for humans (Schrauzer 2002) and most probably other mammals (Anke et al 2005).…”
Section: Resultssupporting
confidence: 68%
“…The results for the reference samples showed recovery rates between 95 and 104 %, demonstrating the appropriateness of the sample preparation used. A detailed list of recovery rates and detection limits was published elsewhere (Otachi et al 2014). Target hazard quotients (THQ) were determined for the trace elements in order to assess the risk to local residents who consume H. forskahlii.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Elevated Se concentrations may also be attributed to As concentrations, as Se functions in As detoxification (Sah et al, 2013). Otachi et al (2014) found higher concentrations of Mn (2.43 µg/g dw) and Zn (604 µg/g dw) and lower concentrations of Cu (0.54 µg/g dw), Fe (14.3 µg/g dw) and Pb (0.024 µg/g dw) in the muscle tissue of Oreochromis leucostictus from Lake Naivasha in comparison to that of L. capensis. The increased levels of Zn in O. leucostictus muscle tissue may be associated with the increased Zn concentrations within the sediment of Lake Naivasha, 229.6 µg/g dw in comparison to 5.8 µg/g dw for the sediment of the Vaal Dam.…”
Section: Fish Tissue Concentrationsmentioning
confidence: 99%